DEVELOPMENT PROBLEMS OF JOINT STOCK COMPANIES IN RUSSIA - Vladimir I. Budarin (Вестник Донского государственного технического университета, 2018)
The problems on th e origin and development of the joint stock companies in Russia are considered. Their form ation, shortcomings and challenges are characterized, the ways of improving their work are outlined t hrough the example of ‘Rostvertol’ JSC.